Examining the Role of Patent Quality in Large-Scale "Patent War" Litigation A Historical Comparison and Proposal for a Restorative U.S. Patent System - Zohni, Wael (Munich Intellectual Property Law Center - MIPLC, 2018)
Although the U.S. Patent System has been essential to spurring innovation, it has wavered in its efficiency and effectiveness at doing so. This research first makes historical comparison and analysis of the Apple and Wright landmark patent war cases to illustrate that, irrespective of timing, benefits of a patent system rest heavily on how well it defines and maintains "patent quality." Much of the challenge in maintaining such quality relates to the subjective and often uncertain nature of invention criteria such as "non-obviousness." As shown by recent trends, decreased patent quality leads to greater uncertainty about patent validity, which in turn invites more litigation. This work proposes that, in order to improve constancy on patent quality, the U.S. patent office should consider returning to original strategies envisioned by the Founders of the United States as described by a patent-registration system that emphasizes utility and public review in governing the patent granting process. Modern information technology can now be applied to effectively restore this original framework envisioned for patent quality control systems.